Monolithic integration of deep ultraviolet LED with a multiplicative photoelectric converter. (December 2019) - Wang, Shuai; Long, Hanling; Zhang, Yi; Chen, Qian; Dai, Jiangnan; Zhang, Shuang; Chen, Jingwen; Liang, Renli; Xu, Linlin; Wu, Feng; Zhang, Zi-Hui; Sun, Haiding; et al.
Abstract: Vertically monolithic integration of multiple devices on a single chip has emerged as a promising approach to overcome the fundamental limits of material and physical properties, providing unique opportunities to harness their complementary physics through integrated solutions to significantly enhance device performance. Herein, we demonstrate a deep ultraviolet light emitting diode (DUV LED) integrated with a multiplicative photoelectric converter (MPC) that is composed of p-GaN/intrinsic GaN/n-GaN (p-i-n GaN) structure to induce the electric-optic conversion, thus considerably improve the hole injection efficiency. This p-i-n GaN structure acts as hole-multiplier via firstly DUV light absorption and then electron-hole pair generation. The newly generated electron-hole pairs are firstly separated by the electric field in the p-i-n GaN structure so that multiple holes are driven into multiple quantum wells (MQWs), and finally contribute to the radiative recombination, thus achieving a high wall plug efficiency (WPE) of 21.6%, which exhibits a 60-fold WPE enhancement compared to the conventional DUV LEDs. The monolithic integration strategy demonstrated here sheds light on developing highly efficient light emitters. Graphical abstract: Monolithic integration of deep ultraviolet (DUV) LED with a multiplicative photoelectric converter (MPC) is demonstrated to considerably improve the hole injection efficiency to be 46, which is known as a fundamental obstacle to high performance DUV emitters. By this means, the MPC- DUV LED shows a high wall plug efficiency (WPE) of 21.6%, which exhibits a 60-fold WPE enhancement compared to the conventional DUV LEDs. Image 1 Highlights: Original monolithic integration device of deep ultraviolet LED with a multiplicative photoelectric converter is proposed. Utilizing the multiplicative photoelectric converter under Geiger mode, carrier injection efficiency is greatly improved. Experimentally achieves a 60-fold enhancement of the wall-plug efficiency for MPC-DUV LED than C-DUV LED.